The Influence of Electronic Service Quality and Trust in Increasing Loyalty Through User Satisfaction: Case Study of the Ministry of Manpower's SIAPkerja Application - Iqbal, Faizul (PT. Maju Malaqbi Makkarana, 2024)
This study aims to (1) examine the direct effect of service quality and user trust on SIAPkerja employment service user satisfaction; (2). examine the direct effect of service quality and user trust on SIAPkerja employment service user loyalty; (3). examine the direct effect of user satisfaction on SIAPkerja employment service user loyalty; and (4). Testing the indirect effect of service quality and user trust on the loyalty of SIAPkerja employment service users through user satisfaction. This study involved 150 users of the Ministry of Manpower's SIAPkerja employment service. Data was obtained through the distribution of questionnaires. Hypothesis testing using Structural Equation Model - Partial Least Square (SEM-PLS) using SmartPLS 3. The results showed that service quality and user trust directly have a positive and significant effect on SIAPkerja employment service user satisfaction; service quality directly has a positive and significant effect on user loyalty. User trust directly has a positive but insignificant effect on user loyalty. User satisfaction directly has a positive and significant effect on user loyalty. Service quality and user trust indirectly have a positive and significant influence on the loyalty of SIAPkerja employment service users through user satisfaction. In other words, user satisfaction mediates the effect of service quality and user trust on the loyalty of SIAPkerja employment service users.